WORLD Intellectual Property Organization : Performances and Phonograms Treaty [adopted in Geneva, December 20, 1996]. (1997)
Presents the text of the Treaty which aims to protect the rights of performers and producers of phonograms, especially in light of recent economic, social, cultural and technological developments.
DC